Public emergency department: the psychosocial impact on the physical domain of quality of life of nursing professionals - Moisés Kogien; José Juliano Cedaro (Universidade de São Paulo, 2014)
OBJECTIVES: to determine the psychosocial factors of work related to harm caused in the physical domain of the quality of life of nursing professionals working in a public emergency department. METHOD: cross-sectional, descriptive study addressing 189 nursing professionals. The Job Stress Scale and the short version of an instrument from the World Health Organization to assess quality of life were used to collect data. Robert Karasek's Demand-Control Model was the reference for the analysis of the psychosocial configuration. The risk for damage was computed with a confidence interval of 95%. RESULTS: In regard to the psychosocial environment, the largest proportion of workers reported low psychological demands (66.1%) and low social support (52.4%), while 60.9% of the professionals experienced work situations with a greater potential for harm: high demand job (22.8%) and passive work (38.1%). CONCLUSIONS: low intellectual discernment, low social support and experiencing a high demand job or a passive job were the main risk factors for damage in the physical domain of quality of life.